شعر اقبال کی متصوفانہ جہات کا تحقیقی مطالعہ: The Mystical aspects of Iqbal’s Poetry: A research Stduy - نقوی, ڈاکٹر رضوانہ; حسین, فضیلت (Tashkeel e Jadeed, 2024)
Allama Mohammad iqbal was a renowned figure of social, political history as well as of literature.It wouldn’t be wrong if we say him a multidimensional personality. In Urdu poetry he is a symbol of philosophical ideas through his present self philosphy’’. Iqbal got a mystical environment from his childhood, his father was the follower of ‘Qadrias’’, so the influence of ‘’Wahdat-ul-Wajood’’ can be seen in his early pieces of poetry, later he turned towards the ‘’Wahdata ul-Shahood’’under the influence of ‘Mujadad Alaf- Saani’ ‘’Asrar-a Khudi ‘’ reflectes all these shades of intellectual change. This effect lives in his poetry for a long time, even in the later part of age another color of harmony starts to prevail .Iqbal has mentioned Sufism at various points of his poetry, along with the importance of Shariat he give more importance to intuition ,theosophy, inner state of emotions and discernment which are the soul of religion. In this article it has been tried to unravel the knots of Iqbal’s mystical poetry to find out the real color of his poetical ecstasy.